Mens en klimaat soos uitgebeeld deur Katherine Graham en Abraham H. de Vries - Meyer, Susan (Tydskrif vir letterkunde, 2025)
This study is focussed on the experience of climate and how to live with it: with its effect on the physically perceptible and also on the imperceptible—the mental or psychological. The concept of climate is not based on natural and scientific facts exclusively. Following ecocritics who consider climate and climate change from a cultural angle, such as Alex Goodbody, Roger Fleming and Vladimir Jankovic, as well as Eva Horn and Solvejg Nitzke, I see climate as a cultural concept. This implies that I investigate the phenomenon of climate as related to experiences of an individual, social and cultural nature, indicative of how people react to climate, how they live in climate-oriented ways, and how they are influenced by climate. Through the lens of ecocriticism, Katherine Graham’s debut novel, Reën vir Stofvlei (2023), and four short stories from an earlier era by Abraham H. de Vries are analysed to determine the effects of climate, as depicted in these texts, on the human body, state of mind and ways of thinking. The importance of this article lies in its formulation of a cultural perspective on climate and on extending research on the literary embodiment of geographical details of South Africa, focusing on the unique nature of Afrikaans ecocriticism. The human-climate association is key to an understanding of the human-nature dynamics in South Africa.